Monooxime Bispyridinium Reactivators Bearing Xylene Linker Synthesis and In Vitro Evaluation on Model of Organophosphate-Inhibited Acetylcholinesterase - Musilek, Kamil; Hambalek, Jan; Holas, Ondrej; Dohnal, Vlastimil; Kuca, Kamil (Medicinal Chemistry, 2016)
Nine novel mono-oxime reactivators bearing xylene linker were synthesized in an effort to improve previously prepared xylene bisoximes and monocarbamoyl-monooximes. The novel compounds were tested in vitro on the model of tabun-, paraoxon-, methylparaoxon- and DFP-inhibited human erythrocyte AChE. Their reactivation ability was compared to pralidoxime, asoxime, obidoxime and two previously prepared xylene linked bisoximes (K107, K108). All compounds showed minimal reactivation of tabun-inhibited AChE at selected concentration scale. This finding was explained by molecular modelling study. Bisoximes obidoxime and K108 resulted as the best reactivators for paraoxon-, methylparaoxon- and DFP-inhibited AChE. The loss of nonoxime moiety lead to the loss of reactivation ability within the novel compounds. Though the novel reactivators did not exceed previously known compounds, they confirmed former SAR findings for xylene-linked AChE reactivators.
Keywords: oxime